2021
DOI: 10.5713/ab.20.0844
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, carcass traits and gut health of broiler chickens fed diets incorporated with single cell protein

Abstract: Objective: This study was conducted to evaluate single cell protein (SCP), produced from Methylococcus species, as a protein source on the growth performance, carcass traits and gut health of broiler chickens.Methods: Ten iso-nitrogenous and iso-caloric diets containing 0 (Control), 2.5%, 5%, 7.5%, and 10% SCP replacing either soybean meal (T1 to T5) or fish meal (T6 to T10) were formulated. Each diet prepared for starter (0 to 14 days), grower (15 to 21 days), and finisher (22 to 42 days) phases was offered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Therefore, it is important to consider the breast and leg muscle yields as they are crucial indicators of meat production performance. Previous research has shown that supplying an appropriate level of SCP in broiler diets can improve carcass quality and increase breast and leg muscle yields (14), which is consistent with the results of this study. Another study reported that the supplement of different proportions of SCP in broiler diets did not affect the dressing percentage, which aligns with the findings of the present study (35).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is important to consider the breast and leg muscle yields as they are crucial indicators of meat production performance. Previous research has shown that supplying an appropriate level of SCP in broiler diets can improve carcass quality and increase breast and leg muscle yields (14), which is consistent with the results of this study. Another study reported that the supplement of different proportions of SCP in broiler diets did not affect the dressing percentage, which aligns with the findings of the present study (35).…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have confirmed that SCP can be used in broiler diets to reduce the need for soybean meal. Furthermore, the appropriate amount of SCP can increase the breast and leg muscle yields while also improving the weight gain, FCR, and economic efficiency of broilers (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…In the poultry industry, it takes at least 42 days for a broiler to reach market size. Compared to the control group, which was fed only SBM, feeding 2.5 or 5% SCP resulted in greater body weight growth over various phases and cumulatively ( 32 ). Additionally, our study showed improvements in ADFI in the beginning phase when CAP was included in Cobb broiler diets.…”
Section: Discussionmentioning
confidence: 99%